Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1993
DOI: 10.1115/93-gt-122
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the 3D Swirling Flow in Centrifugal Compressor Volutes

Abstract: The improvement of centrifugal compressor performance and the control of the radial forces acting on the impeller due to the circumferential variation of the static pressure caused by the volute require a good understanding of the flow mechanisms and an accurate prediction of the flow pattern inside the volute. A 3D volute calculation method has been developed for this purpose. The volute is discretized by means of hexahedral elements. A cell vertex finite volume approach is used in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…of mass flow). Expansion loss decreases up to the design point [3]. Hence, aggregate loss will increase slightly up to the design mass flowrate and spike afterwards, when the choke limit is approached.…”
Section: Influences On Compressor Performance and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…of mass flow). Expansion loss decreases up to the design point [3]. Hence, aggregate loss will increase slightly up to the design mass flowrate and spike afterwards, when the choke limit is approached.…”
Section: Influences On Compressor Performance and Stabilitymentioning
confidence: 99%
“…Detailed measurements by Ayder et al indicated a very complex, threedimensional (3D) flow within the volute and gave fundamental insights for further research [2][3][4]. It is well known that the volute flow causes a rotationally non-symmetric pressure distribution in the diffuser outlet at off-design conditions: the volute acts as a diffuser at lower than design mass flow and as a nozzle at higher than design mass flow, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Future development could be the coupling of the unsteady impeller flow calculation with a volute flow calculation, such as the one by Ayder (1993), to obtain a full stage prediction program.…”
Section: Discussionmentioning
confidence: 99%
“…Ayder et al used a five hole probe to investigate the flow inside an overhang elliptical cross section volute to give a better insight into the three-dimensional flow structure at different mass flow rate conditions [2,3]. They developed a three-dimensional volute calculation method for this purpose to predict the velocity and pressure distribution inside and at the upstream parts of the volute [3].…”
Section: Introductionmentioning
confidence: 99%
“…They developed a three-dimensional volute calculation method for this purpose to predict the velocity and pressure distribution inside and at the upstream parts of the volute [3].…”
Section: Introductionmentioning
confidence: 99%